Slurry containing adhesion promoter and preparation method thereof
By adding non-fluorine long-chain adhesion promoters and organic macromolecules to the lithium-ion battery slurry, the problem of excessive binder usage in traditional slurry is solved, and the energy density and cycle stability of the battery are improved.
Patent Information
- Application Number
- CN202411870648.4
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-12-18
- Publication Date
- 2025-04-11
AI Technical Summary
During the preparation of traditional lithium-ion battery slurry, a large amount of adhesive is used to ensure the adhesion of the electrode material, resulting in a decrease in the battery energy density.
Add non-fluorine long-chain, crystalless long-chain adhesion promoter to the slurry, and supplemented with an appropriate amount of organic macromolecules to enhance the wetting and dispersion of the slurry and improve the adhesion ability of the electrode material and Al foil.
It effectively reduces the amount of binder, improves the energy density and cycle stability of the battery, and maintains the fluidity of the slurry.
Smart Images

Figure BDA0005195677010000091
Abstract
Description
Technical Field
[0001] The present application relates to the technical field of lithium ion battery material preparation, and in particular to a slurry containing an adhesion promoter and a preparation method thereof. Background Art
[0002] With the rapid development of electric vehicles, portable electronic devices and other markets, higher requirements are placed on the energy density and processing performance of lithium-ion batteries. In the traditional slurry preparation process, a large amount of binders (such as PVDF) are used to ensure the adhesion of electrode materials, but this undoubtedly increases the amount of binders used and reduces the energy density of the battery.
[0003] Therefore, it is particularly important to research and develop a slurry that can reduce the amount of binder while ensuring the adhesion and fluidity of the slurry. Summary of the invention
[0004] In view of the shortcomings of the prior art, the present application provides a slurry containing an adhesion promoter and a preparation method thereof. The present application adds a certain amount of non-fluorine long-chain, non-crystalline long-chain adhesion promoter to the slurry, and assists with an appropriate amount of organic macromolecules to make the slurry have good wettability and dispersibility, enhance the adhesion ability of the slurry to the electrode material and Al foil, and thus improve the energy density and cycle stability of the battery.
[0005] In a first aspect, the present application provides a slurry containing an adhesion promoter, using the following technical solution: A slurry containing an adhesion promoter comprises the following raw materials by weight: 93-97 parts of active material, 1.5-2.5 parts of binder, 3-5 parts of conductive agent, 0.3-0.5 parts of adhesion promoter, 0.05-0.5 parts of organic macromolecule, 6-10 parts of N,N-dimethylacetamide and 80-90 parts of NMP, wherein the molecular weight of the organic macromolecule is 1000-50000, and the adhesion promoter is a non-fluorine long-chain, non-crystalline long-chain material.
[0006] By adopting the above technical solutions, active material: As the main energy source of lithium battery, the quality of active material directly affects the energy output and overall performance of the battery. Binder: Binder is used to bind active material, conductive agent and other components together to form a uniform slurry. The selection and dosage of binder directly affect the adhesion of slurry and the energy density of battery. Conductive agent: The main function of conductive agent is to improve the conductivity of slurry, thereby improving the overall performance of battery. Adhesion promoter: Adhesion promoter can greatly reduce the amount of binder, while significantly improving the adhesion of slurry. The selection and dosage of adhesion promoter have an important influence on the energy density and cycle stability of battery. Organic macromolecule: Organic macromolecule is used to enhance the long chain expansion of adhesion promoter and wettability on Al foil surface. This helps to fully rivet the long chain functional groups of adhesion promoter on Al foil, while ensuring the fluidity of slurry. N, N-dimethylacetamide and NMP: These two substances are mainly used to adjust the viscosity and fluidity of slurry to ensure the uniformity and stability of slurry during preparation. The main function of each component in the slurry is to form a uniform slurry with good adhesion and fluidity. The adhesion promoter and organic macromolecules work together to make the slurry have good wettability and dispersibility, and enhance the adhesion of the slurry to the electrode material Al foil. At the same time, the amount of binder is effectively controlled, thereby improving the energy density and cycle stability of the battery.
[0007] Preferably, the organic macromolecule is at least one of alkylammonium salts of acidic copolymers, phosphate esters, alkylammonium salts of copolymers with acidic groups, polysiloxane quaternary ammonium salt-11 tridodecylmethylammonium chloride and styrene-maleic anhydride copolymer.
[0008] Preferably, the adhesion promoter is composed of modified polyacrylonitrile, modified polyacrylate, modified polyimide and modified polyethylene oxide in a mass ratio of 3:5:4:1.5-2.
[0009] By adopting the above technical scheme, the adhesion of the pole piece is significantly improved by introducing an adhesion promoter, which helps to improve the performance stability of the battery. The amount of binder is reduced while ensuring adhesion, thereby improving the energy density of the battery. By adding an appropriate amount of organic macromolecules, the long chain stretching of the adhesion promoter and the rivet of the Al foil are effectively improved to ensure the fluidity of the slurry and the effect of the adhesion promoter. The synergistic effect between modified polyacrylonitrile, modified polyacrylate, modified polyimide and modified polyethylene oxide is mainly reflected in the following aspects: 1. Synergistic effect: These four materials can produce a synergistic effect when compounded in a specific proportion, greatly reducing the amount of binder and significantly improving the adhesion of the slurry. 2. Wetting properties: Alkyl ammonium salts of acidic copolymers, phosphates, alkyl ammonium salts of copolymers with acidic groups, and styrene-butadiene anhydride copolymers can significantly improve their wetting properties, which helps the slurry to better wet the Al foil surface. 3. Processing performance: The modified polyimide is modified with a very flexible organic silicon segment (terminated amino silicone oil), and the resulting product has high toughness and good processing performance during pole piece processing. 4. Adhesion performance: Due to the efficient adhesion of modified polyacrylonitrile, modified polyacrylate, modified polyimide and modified polyethylene oxide, the amount of PVDF used can be reduced while improving the adhesion performance. This helps to reduce the weight of the battery and increase the energy density of the battery, thereby increasing the battery's endurance.
[0010] Preferably, the modified polyacrylonitrile, in parts by mass, comprises: 80-90 parts of a first monomer, the first monomer being at least one of acrylonitrile and methacrylonitrile; 0-15 parts of a second monomer, the second monomer being at least one of an acrylate and a methacrylate monomer; 0-5 parts of a third monomer, the third monomer being a combination of one or more of an olefin acidic monomer, a sodium salt corresponding to an olefin acidic monomer, or a lithium salt corresponding to an olefin acidic monomer; and an emulsifier, deionized water, and an initiator; the second monomer being ethyl acrylate, ethyl methacrylate, propyl acrylate, propyl methacrylate, isopropyl methacrylate, butyl acrylate, butyl methacrylate, methyl A combination of one or more of isobutyl acrylate, isodecyl methacrylate, amyl acrylate, n-amyl methacrylate, isopentyl methacrylate, n-hexyl methacrylate, isooctyl acrylate, isooctyl methacrylate, lauryl acrylate, lauryl methacrylate, octadecyl acrylate, octadecyl methacrylate, methoxypolyethylene glycol methacrylate and ethoxyethyl acrylate; the third monomer is a combination of one or more of acrylic acid, sodium acrylate, lithium acrylate, methacrylic acid, sodium methacrylate, lithium methacrylate, β-acryloxypropionic acid, 2-acrylamide-2-methylpropane sulfonic acid, sodium allyl sulfonate, sodium vinyl sulfonate, sodium allyl sulfonate and sodium styrene sulfonate.
[0011] Preferably, the preparation method of the modified polyacrylonitrile comprises the following steps: (1) Pre-emulsification: the first monomer, the second monomer, and the third monomer are uniformly mixed, and then an emulsifier and deionized water are added to pre-emulsify to obtain a mixed emulsion; (2) heating the pre-emulsified mixed emulsion in step (1) to the reaction temperature and stirring the reaction, adding an initiator dropwise for 1 hour, and keeping the temperature for 4 hours to obtain a preliminary emulsion; (3) filtering, neutralizing, and cooling the preliminary emulsion obtained in step (2) to obtain a polymer emulsion; (4) drying the polymer emulsion obtained in step (3) to obtain a solid powder; (5) The solid powder obtained in step (4) is washed, purified, dried and sieved to obtain modified polyacrylonitrile.
[0012] Preferably, the preparation method of the modified polyimide comprises the following preparation steps: S61. Under nitrogen protection, 0.1 mol of amino-terminated silicone oil with a number average molecular weight of 2000, 0.25 mol of hexamethylene diisocyanate and 1500 g of N,N-dimethylformamide were mixed, and polymerization reaction was carried out at 30° C. for 6 hours to obtain a prepolymer; S62, while the prepolymer is being stirred, 0.1 mol of hexamethylene diisocyanate and 0.24 mol of 4,4'-phenylenedioxydiphthalic anhydride are added, the temperature is raised to 100° C. and the polymerization reaction is carried out for 8 hours to obtain a modified polyimide.
[0013] By adopting the above technical scheme, the preparation method of modified polyimide includes two steps, aiming to synthesize a silicone modified polyimide material with excellent performance through specific chemical reactions and control of conditions. This method not only improves the toughness, heat resistance, insulation and mechanical strength of the material, but also significantly improves the adhesion of PVDF through the synergistic effect with modified polyacrylonitrile, modified polyacrylate and modified polyethylene oxide, and reduces the amount of PVDF in lithium-ion batteries, thereby improving the energy density and cycle stability of the battery. Step S41: Preparation of prepolymer, in this step, a prepolymer containing an isocyanate group is formed by the reaction of terminal amino silicone oil with hexamethylene diisocyanate. This step is the key starting point for the preparation of modified polyimide and provides the necessary chemical basis for the subsequent imidization reaction. Step S42: Synthesis of modified polyimide, in this step, the prepolymer further undergoes imidization reaction with 4,4'-phenylenedioxydiphthalic anhydride and hexamethylene diisocyanate to form a silicone modified polyimide. This material combines the flexibility of silicone with the heat resistance, insulation and mechanical strength of polyimide, providing a solid material foundation for improving PVDF adhesion and battery performance.
[0014] Preferably, the preparation method of the modified polyacrylate is as follows: according to the mass fractions, in a four-necked reaction flask equipped with a stirrer, a thermometer, a reflux condenser, and a constant pressure dropping funnel, 0.5 parts of sodium dodecylbenzene sulfonate and 553.3 parts of deionized water are added, stirred and completely dissolved, nitrogen is introduced, and then 90 parts of butyl acrylate, 4-5 parts of acrylonitrile and 5 parts of lithium methacrylate are added for pre-emulsification for 0.5-1h, and then under the protection of nitrogen, the temperature is raised to a reaction temperature of 60-65°C, 0.4 parts of ammonium persulfate are slowly added dropwise within 1h, and the reaction is continued for 4-5h of insulation, and after the reaction is completed, an appropriate amount of ammonia water is added to neutralize to a pH of 7-7.5, the product is filtered, and the obtained polymer emulsion is spray-dried to obtain a solid powder, and the solid powder is washed with deionized water, dried, crushed, and sieved to prepare the modified polyacrylate.
[0015] Preferably, the preparation method of the modified polyethylene oxide is as follows: according to the mass fractions, 100 parts of polyethylene oxide and 250 parts of N-methylpyrrolidone are added into a reactor and mixed evenly, and then 3 parts of fatty acid ester-based polyethylene oxide are added dropwise at a rate of 0.3 parts / min under stirring at 250-300 r / min, and then reacted at 25°C for 2-2.5h, and then N-methylpyrrolidone is removed by suction filtering, and vacuum dried at 30°C for 12-14h to obtain the modified polyethylene oxide.
[0016] By adopting the above technical scheme, polyethylene oxide can be modified by fatty acid ester polyethylene oxide to significantly improve its wetting properties. The improvement of wetting properties helps the slurry to better disperse and adhere to the electrode material Al foil, thereby improving the energy density and cycle stability of the battery. The modified polyethylene oxide can effectively improve the adhesion of the slurry. Through the synergistic effect with other adhesion promoters and organic macromolecules, the amount of binder can be greatly reduced, while the adhesion of the slurry can be significantly improved. This helps to reduce the weight of the battery and improve the energy density and endurance of the battery. Due to the efficient adhesion and synergistic effect of the modified polyethylene oxide, the amount of PVDF used can be reduced. This not only helps to reduce the weight of the battery, but also improves the energy density and endurance of the battery. In general, the role of modified polyethylene oxide in the slurry is multifaceted. It not only improves the wettability and adhesion of the slurry, but also improves the overall performance of the battery through synergistic effects with other components. This improvement is of great significance for improving the energy density, cycle stability and endurance of the battery.
[0017] Preferably, the active material is at least one of lithium cobalt oxide, lithium manganese oxide, nickel-cobalt-manganese ternary material and lithium iron phosphate; the conductive agent is at least one of carbon nanotubes, graphene, carbon black and conductive graphite; and the binder is PVDF powder.
[0018] In a second aspect, the present application provides a method for preparing a slurry containing an adhesion promoter, using the following technical solution: As a general technical concept, the present application also provides a method for preparing the above-mentioned slurry containing an adhesion promoter, comprising the following steps: S101, mixing the active material and the conductive agent according to their weight fractions at a stirring speed of 100-150 rpm for 5-10 minutes to obtain a mixture; S102, dissolving a binder, an organic macromolecule and an adhesion promoter in N,N-dimethylacetamide according to their weight fractions to obtain a mixed solution; S103, stirring and mixing the mixture, the mixed solution and NMP uniformly according to the mass fractions, filtering and degassing to obtain a slurry containing an adhesion promoter.
[0019] In summary, the present application includes at least one of the following beneficial technical effects: 1. Improve adhesion: By introducing non-fluorine long-chain, non-crystalline long-chain adhesion promoter, the adhesion of the electrode sheet is significantly improved. This adhesion promoter can effectively enhance the adhesion of the slurry to the electrode material Al foil.
[0020] 2. Reduce the amount of binder: Under the premise of ensuring adhesion, the amount of binder is reduced. This not only reduces production costs, but also increases the energy density of the battery.
[0021] 3. Maintain fluidity: By adding an appropriate amount of organic macromolecules, the expansion of the long chain of the adhesion promoter and the wettability of the Al foil surface are effectively improved. This ensures the fluidity of the slurry, allowing the slurry to maintain good dispersion and stability during processing.
[0022] 4. Improve battery performance: The slurry prepared by the present application can improve the overall performance of lithium-ion batteries, including energy density, cycle stability and safety, etc. This is of great significance for improving the overall performance and service life of the battery.
[0023] 5. Reduce battery weight: Due to the efficient adhesion of modified polyacrylonitrile, modified polyacrylate, modified polyimide and modified polyethylene oxide, the amount of PVDF used can be reduced while improving the adhesion performance. This helps to reduce the weight of the battery, increase the energy density of the battery, and thus increase the battery's endurance.
[0024] 6. Improve processing performance: The modified polyimide is modified with a very flexible silicone segment, and the resulting product has high toughness and good processing performance during pole piece processing. This helps to improve production efficiency and product quality. DETAILED DESCRIPTION
[0025] The embodiments of the present application will be described in detail below in conjunction with the examples, but it will be appreciated by those skilled in the art that the following examples are only used to illustrate the present application and should not be considered as limiting the scope of the present application. If the specific conditions are not specified in the examples, the conditions recommended by the manufacturer are carried out according to normal conditions. If the manufacturer is not specified for the reagents or instruments used, they are all conventional products that can be purchased commercially. Styrene-maleic anhydride copolymer is purchased from Shanghai Yijing Industrial Co., Ltd.
[0026] In the following Examples and Preparation Examples, 1 part means 10 g.
[0027] Preparation Example 1 Preparation of modified polyacrylonitrile In a four-necked reaction flask equipped with a stirrer, a thermometer, a reflux condenser, and a constant pressure dropping funnel, an emulsifier (sodium dodecyl sulfate, 0.5 g) and a solvent (H 2 O, 553.3g), stirred and dissolved completely, nitrogen was introduced, and then the first monomer (acrylonitrile, 90g), the second monomer (butyl acrylate, 5g), and the third monomer (lithium methacrylate, 5g) were added and pre-emulsified for 0.5h, and then in an inert gas N 2 Under protection, the temperature was raised to 60°C, an initiator (ammonium persulfate, 0.4 g) was added dropwise for 1 hour, and the reaction was continued for 4 hours. After the reaction was completed, an appropriate amount of ammonia water was added to neutralize the pH to 7, the product was filtered, and the obtained polymer emulsion was spray-dried to obtain a solid powder. The solid powder was washed with deionized water, dried, crushed, and sieved to prepare modified acrylonitrile.
[0028] Preparation Example 2 Preparation of modified polyimide The preparation method of modified polyimide comprises the following preparation steps: S61. Under nitrogen protection, 0.1 mol of amino-terminated silicone oil with a number average molecular weight of 2000, 0.25 mol of hexamethylene diisocyanate and 1500 g of N,N-dimethylformamide were mixed, and polymerization reaction was carried out at 30° C. for 6 hours to obtain a prepolymer; S62, while the prepolymer is being stirred, 0.1 mol of hexamethylene diisocyanate and 0.24 mol of 4,4'-phenylenedioxydiphthalic anhydride are added, the temperature is raised to 100° C. and the polymerization reaction is carried out for 8 hours to obtain a modified polyimide.
[0029] Preparation Example 3 Preparation of modified polyacrylate The preparation method of modified polyacrylate is as follows: according to the mass fractions, in a four-necked reaction flask equipped with a stirrer, a thermometer, a reflux condenser and a constant pressure dropping funnel, 0.5 parts of sodium dodecylbenzene sulfonate and 553.3 parts of deionized water are added, stirred and completely dissolved, nitrogen is introduced, and then 90 parts of butyl acrylate, 4.5 parts of acrylonitrile and 5 parts of lithium methacrylate are added for pre-emulsification for 0.7 hours, and then under the protection of nitrogen, the temperature is raised to a reaction temperature of 62°C, 0.4 parts of ammonium persulfate are slowly added dropwise within 1 hour, and the heat preservation reaction is continued for 4.5 hours. After the reaction is completed, an appropriate amount of ammonia water is added to neutralize to a pH of 7.2, the product is filtered, and the obtained polymer emulsion is spray-dried to obtain a solid powder, and the solid powder is washed with deionized water, dried, crushed and sieved to prepare the modified polyacrylate.
[0030] Preparation Example 4 Preparation of modified polyethylene oxide The preparation method of modified polyethylene oxide is as follows: according to the mass parts, 100 parts of polyethylene oxide and 250 parts of N-methylpyrrolidone are added into a reactor and mixed evenly, and then 3 parts of fatty acid ester polyoxyethylene are added dropwise at a rate of 0.3 parts / min under stirring at 300r / min, and then reacted at 25°C for 2.2h, and then N-methylpyrrolidone was removed by suction, and vacuum dried at 30°C for 13h to obtain modified polyethylene oxide.
[0031] Example 1 A slurry containing an adhesion promoter, comprising the following raw materials by weight: 93 parts of lithium cobalt oxide, 1.5 parts of PVDF powder, 3 parts of carbon nanotubes, 0.3 parts of adhesion promoter, 0.05 parts of phosphate, 6 parts of N,N-dimethylacetamide, and 80 parts of NMP, wherein the adhesion promoter is composed of modified polyacrylonitrile, modified polyacrylate, modified polyimide, and modified polyethylene oxide in a weight ratio of 3:5:4:1.5; The method for preparing the slurry containing the adhesion promoter comprises the following steps: S101, mixing lithium cobalt oxide and carbon nanotubes according to their weight fractions at a stirring speed of 100 rpm for 10 minutes to obtain a mixture; S102, dissolving PVDF powder, phosphate ester and adhesion promoter in N,N-dimethylacetamide according to parts by mass to obtain a mixed solution; S103, stirring and mixing the mixture, the mixed solution and NMP uniformly according to the mass fractions, filtering and degassing to obtain a slurry containing an adhesion promoter.
[0032] Example 2 A slurry containing an adhesion promoter, comprising the following raw materials by weight: 97 parts of lithium cobalt oxide, 2.5 parts of PVDF powder, 5 parts of graphene, 0.5 parts of adhesion promoter, 0.5 parts of styrene-maleic anhydride copolymer, 10 parts of N,N-dimethylacetamide, and 90 parts of NMP, wherein the adhesion promoter is composed of modified polyacrylonitrile, modified polyacrylate, modified polyimide, and modified polyethylene oxide in a weight ratio of 3:5:4:2; The method for preparing the slurry containing the adhesion promoter comprises the following steps: S101, mixing lithium cobalt oxide and graphene at a stirring speed of 150 rpm for 5 minutes according to their mass fractions to obtain a mixture; S102, dissolving PVDF powder, styrene-maleic anhydride copolymer and an adhesion promoter in N,N-dimethylacetamide according to their mass fractions to obtain a mixed solution; S103, stirring and mixing the mixture, the mixed solution and NMP uniformly according to the mass fractions, filtering and degassing to obtain a slurry containing an adhesion promoter.
[0033] Example 3 A slurry containing an adhesion promoter comprises the following raw materials by weight: 95 parts of lithium cobalt oxide, 2 parts of PVDF powder, 4 parts of conductive graphite, 0.4 parts of adhesion promoter, 0.02 parts of polysiloxane quaternary ammonium salt-11 tridodecylmethylammonium chloride, 8 parts of N,N-dimethylacetamide, and 85 parts of NMP, wherein the adhesion promoter is composed of modified polyacrylonitrile, modified polyacrylate, modified polyimide, and modified polyethylene oxide in a weight ratio of 3:5:4:1.8; The method for preparing the slurry containing the adhesion promoter comprises the following steps: S101, mixing lithium cobalt oxide and conductive graphite according to their weight fractions at a stirring speed of 130 rpm for 8 minutes to obtain a mixture; S102, dissolving PVDF powder, polysiloxane quaternary ammonium salt-11 tridodecylmethylammonium chloride and an adhesion promoter in N,N-dimethylacetamide according to their weight fractions to obtain a mixed solution; S103, stirring and mixing the mixture, the mixed solution and NMP uniformly according to the mass fractions, filtering and degassing to obtain a slurry containing an adhesion promoter.
[0034] Example 4 The same as Example 3, except that: a mixture prepared by equal amounts of polysiloxane quaternary ammonium salt-11 tridecylmethyl ammonium chloride, phosphate ester and styrene-maleic anhydride copolymer in a mass ratio of 1:1:2 is used to replace polysiloxane quaternary ammonium salt-11 tridecylmethyl ammonium chloride.
[0035] Comparative Example 1 The same as Example 4, except that: the adhesion promoter is modified polyacrylonitrile.
[0036] Comparative Example 2 The same as Example 4, except that: the adhesion promoter is modified polyacrylate.
[0037] Comparative Example 3 The same as Example 4, except that: the adhesion promoter is modified polyimide.
[0038] Comparative Example 4 The same as Example 4, except that the adhesion promoter is modified polyethylene oxide.
[0039] Performance testing The slurries containing adhesion promoters prepared from the above-mentioned Examples 1 to 4 and Comparative Examples 1 to 4 were used to prepare positive electrode sheets and lithium-ion batteries. The details are as follows: (1) Preparation of positive electrode sheets The slurry containing the adhesion promoter is evenly coated on the positive electrode current collector aluminum foil, and the positive electrode sheet is obtained through drying, hot pressing and slitting.
[0040] (2) Preparation of negative electrode sheets The active material graphite, conductive carbon SP, thickener sodium carboxymethyl cellulose (CMC), and binder styrene butadiene rubber (SBR) are dissolved in deionized water at a weight ratio of 96.5:1:1:1.5, mixed evenly to prepare a negative electrode slurry, and the slurry is evenly coated on the negative electrode current collector copper foil, and the negative electrode sheet is obtained after drying, cold pressing, and slitting.
[0041] (3) Preparation of diaphragm Using PE porous polymer film as separator (4) Preparation of electrolyte Lithium hexafluorophosphate was dissolved in a carbonate solvent (ethylene carbonate, propylene carbonate, and ethyl methyl carbonate in a volume ratio of 2:2:2) to prepare a 1 mol / L electrolyte.
[0042] (5) Preparation of batteries The positive electrode sheet, separator and negative electrode sheet are wound in order to obtain a battery cell. The battery cell is packaged with an aluminum plastic film, baked at 85°C for 24 hours, and injected with electrolyte after dehydration. After vacuum packaging, shelving, formation, secondary sealing, shaping and other processes, a lithium-ion battery is obtained.
[0043] (6) Battery cycle test at room temperature The lithium-ion battery was charged to 4.35V at 1C constant current, then charged to a cut-off current of 0.02C at 4.35V, left for 5 minutes, and then discharged to 3.0V at 1C constant current, left for 5 minutes, and the first cycle discharge capacity was measured. After 500 cycles of charge / discharge, the 500th cycle discharge capacity was measured, and the 500th cycle capacity retention rate was calculated using the following formula: 500th cycle capacity retention rate (%) = (500th cycle discharge capacity / first cycle discharge capacity) × 100%. The specific results are shown in Table 1.
[0044] (7) Peel strength test: The prepared positive electrode sheet was cut into 10 cm × 2 cm strips and fixed to a 1 mm steel plate with double-sided tape on the current collector side. A transparent tape was pasted on the coating layer side. A 180° pulling peeling test was performed at a peeling speed of 100 mm / min using a universal electronic testing machine at 25°C. The peeling stress was recorded. The specific results are shown in Table 1.
[0045] Table 1 Performance test Analyzing the data in Table 1, we can see that: 1) The performance of the slurries containing adhesion promoters prepared in Examples 1 to 4 shows that the present application adds a certain amount of non-fluorine long-chain, non-crystalline long-chain adhesion promoters to the slurry, and assists with the action of an appropriate amount of organic macromolecules, so that the slurry has good wettability and dispersibility, enhances the adhesion ability of the slurry to the electrode material Al foil, and thus improves the energy density and cycle stability of the battery.
[0046] 2) The performance comparison analysis of the slurry containing the adhesion promoter prepared in Example 4 and Example 3 shows that the use of an equal amount of a mixture prepared by polysiloxane quaternary ammonium salt-11 tridecylmethyl ammonium chloride, phosphate ester and styrene-butadiene anhydride copolymer in a mass ratio of 1:1:2 as an organic macromolecule, and the use of the synergistic effect between polysiloxane quaternary ammonium salt-11 tridecylmethyl ammonium chloride, phosphate ester and styrene-butadiene anhydride copolymer, can significantly improve the overall performance of the battery.
[0047] 3) The performance comparison analysis of the slurry containing adhesion promoters obtained in Example 4 and Comparative Examples 1-4 shows that the adhesion promoter is composed of modified polyacrylonitrile, modified polyacrylate, modified polyimide and modified polyethylene oxide in a mass fraction ratio of 3:5:4:1.8. By introducing the adhesion promoter, the adhesion of the pole piece is significantly improved, which helps to improve the performance stability of the battery. The amount of binder is reduced while ensuring adhesion, thereby improving the energy density of the battery. By adding an appropriate amount of organic macromolecules, the long chain stretching of the adhesion promoter and the rivet of the AL foil are effectively improved to ensure the fluidity of the slurry and the adhesion promoter. The joint action between modified polyacrylonitrile, modified polyacrylate, modified polyimide and modified polyethylene oxide is mainly reflected in the following aspects: 1. Synergistic effect: The compounding of these four materials in a specific ratio can produce a synergistic effect, greatly reducing the amount of binder and significantly improving the adhesion of the slurry. 2. Wetting performance: Polyethylene oxide can significantly improve its wetting performance through fatty acid ester polyethylene oxide, which helps the slurry to better wet the surface of the AL foil. 3. Processing performance: Modified polyimide is modified with a very flexible silicone segment (terminated amino silicone oil). The resulting product has high toughness and has good processing performance during pole piece processing. 4. Adhesion performance: Due to the efficient adhesion of modified polyacrylonitrile, modified polyacrylate, modified polyimide and modified polyethylene oxide, the amount of PVDF used can be reduced while improving adhesion performance. This helps to reduce the weight of the battery and increase the energy density of the battery, thereby increasing the battery's endurance.
[0048] The above embodiments are only used to explain the technical solutions of the present application rather than to limit them. Although the above embodiments provide a specific description of the present application, relevant technical personnel should understand that the specific implementation methods of the present application can still be modified or replaced by equivalents, and any modifications and equivalent replacements that do not depart from the spirit and scope of the present application should be included in the protection scope of the present application.
Claims
1. A slurry containing an adhesion promoter, characterized in that: The preparation raw materials include the following by weight: 93-97 parts of active material, 1.5-2.5 parts of binder, 3-5 parts of conductive agent, 0.3-0.5 parts of adhesion promoter, 0.05-0.5 parts of organic macromolecule, 6-10 parts of N,N-dimethylacetamide and 80-90 parts of NMP, wherein the molecular weight of the organic macromolecule is 1000-50000, and the adhesion promoter is a non-fluorine long-chain, non-crystalline long-chain material.
2. A slurry containing an adhesion promoter according to claim 1, characterized in that: The organic macromolecule is at least one of alkylammonium salt of acidic copolymer, phosphate ester, alkylammonium salt of copolymer with acidic group and styrene-maleic anhydride copolymer.
3. The slurry containing an adhesion promoter according to claim 1, characterized in that: The adhesion promoter is composed of modified polyacrylonitrile, modified polyacrylate, modified polyimide and modified polyethylene oxide in a mass ratio of 3:5:4:1.5-2.
4. A slurry containing an adhesion promoter according to claim 3, characterized in that: The modified polyacrylonitrile is prepared from raw materials, in parts by mass: 80-90 parts of a first monomer, which is at least one of acrylonitrile and methacrylonitrile; 0-15 parts of a second monomer, which is at least one of an acrylate and a methacrylate monomer; 0-5 parts of a third monomer, which is a combination of one or more of an olefin acidic monomer, a sodium salt corresponding to an olefin acidic monomer, or a lithium salt corresponding to an olefin acidic monomer; and an emulsifier, deionized water, and an initiator; the second monomer is ethyl acrylate, ethyl methacrylate, propyl acrylate, propyl methacrylate, isopropyl methacrylate, butyl acrylate, butyl methacrylate, methyl methacrylate, ethyl acrylate, propyl methacrylate, isopropyl methacrylate, butyl acrylate, butyl methacrylate, methyl methacrylate, ethyl methacrylate, propyl ... The third monomer is a combination of one or more of isobutyl acrylate, isodecyl methacrylate, amyl acrylate, n-amyl methacrylate, isopentyl methacrylate, n-hexyl methacrylate, isooctyl acrylate, isooctyl methacrylate, lauryl acrylate, lauryl methacrylate, octadecyl acrylate, octadecyl methacrylate, methoxy polyethylene glycol methacrylate and ethoxyethyl acrylate; the third monomer is a combination of one or more of acrylic acid, sodium acrylate, lithium acrylate, methacrylic acid, sodium methacrylate, lithium methacrylate, β-acryloxypropionic acid, 2-acrylamide-2-methylpropane sulfonic acid, sodium allyl sulfonate, sodium vinyl sulfonate, sodium allyl sulfonate and sodium styrene sulfonate.
5. A slurry containing an adhesion promoter according to claim 4, characterized in that: The preparation method of the modified polyacrylonitrile comprises the following steps: (1) Pre-emulsification: After the first monomer, the second monomer and the third monomer are uniformly mixed, an emulsifier and deionized water are added for pre-emulsification to obtain a mixed emulsion; (2) heating the pre-emulsified mixed emulsion in step (1) to the reaction temperature and stirring the reaction, adding the initiator dropwise for 1 hour, and keeping the temperature for 4 hours to obtain a preliminary emulsion; (3) filtering, neutralizing and cooling the preliminary emulsion obtained in step (2) to obtain a polymer emulsion; (4) drying the polymer emulsion obtained in step (3) to obtain a solid powder; (5) The solid powder obtained in step (4) is washed, purified, dried, and sieved to obtain modified polyacrylonitrile.
6. The slurry containing an adhesion promoter according to claim 3, characterized in that: The preparation method of the modified polyimide comprises the following preparation steps: S61. Under nitrogen protection, 0.1 mol of amino-terminated silicone oil with a number average molecular weight of 2000, 0.25 mol of hexamethylene diisocyanate and 1500 g of N,N-dimethylformamide were mixed, and polymerization reaction was carried out at 30° C. for 6 hours to obtain a prepolymer; S62, while the prepolymer is being stirred, 0.1 mol of hexamethylene diisocyanate and 0.24 mol of 4,4'-phenylenedioxydiphthalic anhydride are added, the temperature is raised to 100° C. and the polymerization reaction is carried out for 8 hours to obtain a modified polyimide.
7. The slurry containing an adhesion promoter according to claim 3, characterized in that: The preparation method of the modified polyacrylate comprises the following steps: according to the mass fractions, in a four-necked reaction flask equipped with a stirrer, a thermometer, a reflux condenser and a constant pressure dropping funnel, 0.5 parts of sodium dodecylbenzene sulfonate and 553.3 parts of deionized water are added, stirred and completely dissolved, nitrogen is introduced, and then 90 parts of butyl acrylate, 4-5 parts of acrylonitrile and 5 parts of lithium methacrylate are added for pre-emulsification for 0.5-1h, and then the temperature is raised to a reaction temperature of 60-65°C under the protection of nitrogen, 0.4 parts of ammonium persulfate are slowly added dropwise within 1h, and the reaction is continued for 4-5h with heat preservation, and after the reaction is completed, an appropriate amount of ammonia water is added to neutralize to a pH of 7-7.5, the product is filtered to obtain a polymer emulsion, the obtained polymer emulsion is spray-dried to obtain a solid powder, and the solid powder is washed with deionized water, dried, crushed and sieved to prepare the modified polyacrylate.
8. The slurry containing an adhesion promoter according to claim 3, characterized in that: The preparation method of the modified polyethylene oxide is as follows: according to the mass fractions, 100 parts of polyethylene oxide and 250 parts of N-methyl pyrrolidone are added into a reactor and mixed evenly, and then 3 parts of fatty acid ester-based polyethylene oxide are added dropwise at a speed of 0.3 parts / min under stirring at 250-300 r / min, and then reacted at 25° C. for 2-2.5 hours, and then N-methyl pyrrolidone is removed by suction filtration, and vacuum dried at 30° C. for 12-14 hours to obtain the modified polyethylene oxide.
9. The slurry containing an adhesion promoter according to claim 1, characterized in that: The active material is at least one of lithium cobalt oxide, lithium manganese oxide, nickel-cobalt-manganese ternary material and lithium iron phosphate; the conductive agent is at least one of carbon nanotubes, graphene, carbon black and conductive graphite; and the binder is PVDF powder.
10. A method for preparing a slurry containing an adhesion promoter as claimed in any one of claims 1 to 9, characterized in that: The following steps are involved: S101, mixing the active material and the conductive agent according to their weight fractions at a stirring speed of 100-150 rpm for 5-10 minutes to obtain a mixture; S102, dissolving a binder, an organic macromolecule and an adhesion promoter in N,N-dimethylacetamide according to their weight fractions to obtain a mixed solution; S103, stirring and mixing the mixture, the mixed solution and NMP uniformly according to the mass fractions, filtering and degassing to obtain a slurry containing an adhesion promoter.